NudE regulates dynein at kinetochores but is dispensable for other dynein functions in the C. elegans early embryo - Simões, PA (2018)
In mitosis, themolecular motor dynein is recruited to kinetochores by the Rod-Zw10-Zwilch complex (RZZ) and Spindly to control spindle assembly checkpoint (SAC) signaling and microtubule attachment. How the ubiquitous dynein co-factors Lis1 and NudE contribute to these functions remains poorly understood. Here, we show that the C. elegans NudE homolog NUD-2 is dispensable for dynein- and LIS-1-dependent mitotic spindle assembly in the zygote. This facilitates functional characterization of kinetochore-localized NUD-2, which is recruited by the CENP-F-like proteins HCP-1 and HCP-2 independently of RZZ- Spindly and dynein-LIS-1. Kinetochore dynein levels are reduced in ¿nud-2 embryos, and, as occurs upon RZZ inhibition, loss of NUD-2 delays the formation of load-bearing kinetochore-microtubule attachments and causes chromatin bridges in anaphase. Survival of ¿nud-2 embryos requires a functional SAC, and kinetochores without NUD-2 recruit an excess of SAC proteins. Consistent with this, SAC signaling in early ¿nud-2 embryos extends mitotic duration and prevents high rates of chromosome mis-segregation. Our results reveal that both NUD-2 and RZZ-Spindly are essential for dynein function at kinetochores, and that the gain in SAC strength during early embryonic development is relevant under conditions that mildly perturb mitosis.